Polycation Li-boracite, glass ceramic composition and lithium ion battery
By introducing multi-dopant substances at the B3+ sites in lithium-ion batteries, a thermodynamically stable Li-square borosite phase is solved, and the problem of difficulty in taking into account high energy density, high ion conductivity and stability of existing materials is achieved, and more efficient lithium-ion battery performance is achieved.
Patent Information
- Application Number
- CN202411528656.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-01-26
- Filing Date
- 2024-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
In existing lithium-ion batteries, materials with high energy density and high ionic conductivity are difficult to achieve while maintaining environmental, chemical and electrochemical stability.
By introducing multi-dopant substances at the B3+ site, a new Li-cubestone composition is formed, and the configuration entropy is increased to form a thermodynamically stable Li-cubestone phase.
The previously unknown thermodynamic stability is achieved, improving Li ion conductivity and stability to moisture, while reducing material costs.
Smart Images

Figure CN119911922A_ABST
Abstract
Description
[0001] This application is based on and claims priority to U.S. Provisional Application No. 63 / 546,660 filed in the U.S. Patent and Trademark Office on October 31, 2023 and U.S. Patent Application No. 18 / 424,425 filed on January 26, 2024, the disclosures of which are incorporated herein by reference in their entirety. Technical Field
[0002] A material according to an embodiment relates to a solid electrolyte material for a lithium (Li) solid-state battery. Background Art
[0003] In order to reduce the production of carbon dioxide in our society, the demand for rechargeable batteries has increased dramatically. Among rechargeable batteries, lithium-ion batteries have been utilized in these applications due to their highest energy density. However, achieving high ionic conductivity (or "conductivity") materials with higher energy density with appropriate environmental stability, chemical stability, and electrochemical stability has been an ongoing challenge.
[0004] The general formula is Li 4+x B 7 O 12+x X y The lithium boracite crystal has been identified as a promising Li-ion conductor in all-solid-state batteries, where X is a monovalent anion or a divalent anion. When x = 0 and X = Cl (Li 4 B 7 O 12 Cl cubic space group), the conductivity is highest at room temperature. Partial substitution of X with other X's is also possible and usually results in another phase that is stabilized at room temperature and a sudden drop in conductivity near room temperature.
[0005] Currently, doping of boron sites (Li 4 B 4 Al 3 O 12 Cl) leads to the formation of a glass-ceramic that is stable against Li metal and has a relative high Li / Li + The wide electrochemical window between 0 V and 6 V and the Li + Ion transport number.
[0006] However, despite the structural diversity of borax, the substitution of the BO framework with other cations has only been investigated for Al / Ga dopants. In practice, such substitution of the BO framework is highly difficult or often impossible, mainly because B is a highly cation-free cation compared to other cations. 3+ The very small ionic radius of the site.
[0007] The information disclosed in this background technology section is already known to the inventor before the disclosure of this application or is technical information acquired in the process of disclosure. Therefore, it may contain information that does not form the prior art known to the public. Summary of the invention
[0008] The present disclosure focuses on the development of new Li-boronite compositions in which multiple dopant species are introduced into the B 3+ sites lead to a previously unknown thermodynamically stable Li-boronite phase.
[0009] The present disclosure relates to a parent cubic structure Li 4 B 7 O 12 A non-obvious doping strategy for Cl, in which the parent lithium chloroboracite Li 4 B 7 O 12 Tetrahedral BO in Cl 4 The units are partially or completely substituted. These non-obvious substituted compounds are 2 OB 2 O 3 -M x O y -LiCl high-dimensional system as a stable primary phase in a high-crystalline glass-ceramic, where M can be a trivalent species, or a mixture of divalent, trivalent, tetravalent or pentavalent species. Therefore, the compounds of the present disclosure can generally take the following chemical forms: 4-x B 7-y M y O 12-z Cl w , where Li vacancies, O vacancies, and Cl vacancies are allowed, and M can be a mono-, di-, or ternary combination of the following substances: Al 3+ , Fe 3+ , B 3+ ,La 3+ , Y 3+ 、Mo 3+ 、Be 2+, Si 4+ , Cr 3+ , As 3+ , Mn 2 + , V 2+ , Co 2+ , Ge 2+ , Fe 2+ , Mo 4+ , Mo 6+ , As 3- , Ti 2+ , P 5+ , As 0+ . Here, 0 < x < 2, 0 < y < 6, 0 < z < 1, 0 < w < 2 can satisfy the charge balance mechanism with their respective defect sites (B 3+ , Li + , O 2- or Cl - ), or any combination that satisfies the charge neutrality of the entire composition. The multi-material doping of concurrent B 3+ sites and the generation of vacancies of Li, O, or Cl increase the configurational entropy (i.e., ~100 meV / atom), which subsequently increases the thermodynamic stability of non-obvious substances at the B 3+ sites.
[0010] This disclosure demonstrates several ways to optimize the Li-boracite composition by doping the B 3+ sites to maximize the content of previously unknown elements and cheaper elements.
[0011] This disclosure provides a compound of the formula Li 4-x B 7-y M y O 12-z Cl w ,
[0012] wherein M can be a trivalent substance, or a mixture of divalent, trivalent, tetravalent, or pentavalent substances,
[0013] wherein M can be a monovalent combination, divalent combination, or trivalent combination of the following substances: Al 3+ , Fe 3+ , B 3+ , La 3+ , Y 3 + , Mo 3+ , Be 2+ , Si 4+ , Cr 4+ , As 3+ , Mn 2+ , V 2+ , Co2+ 、Ge 2+ 、Fe 2+ 、Mo 4+ 、Mo 6+ 、As 3- 、Ti 2+ 、P 5+ 、As 0+ ,
[0014] Among them, 0 < x < 2, 0 < y < 6, 0 < z < 1, 0 < w < 2 can satisfy the charge balance mechanism with their respective defect sites (B 3+ 、Li + 、O 2- or Cl - ), or any combination that satisfies the charge neutrality of the entire composition, and
[0015] Among them, the formula is Li 8 Y 4 B 9 Mo(ClO 12 ) 2 、Li 8 Y 4 CrB 9 (ClO 12 ) 2 or Li 8 Y 3 B 8 Mo 3 (ClO 12 ) 2 。
[0016] Embodiments of the present disclosure include compounds of the formula Li 4-x B 7-y M y O 12-z Cl w wherein Li vacancies, O vacancies, and Cl vacancies are allowed, and M is a monadic combination, dyadic combination, or triadic combination of the following substances: Al 3+ 、Fe 3+ 、B 3+ 、La 3+ 、Y 3+ 、Mo 3 + 、Be 2+ 、Si 4+ 、Cr 4+ 、As 3+ 、Mn 2+ 、V 2+ 、Co 2+ 、Ge 2+ 、Fe2+ , Mo 4+ , Mo 6+ , As 3- , Ti 2+ , P 5+ , As 0+ , and wherein, 0 ≤ x < 2, 0 < y < 6, 0 ≤ z < 1, and 0 < w < 2 satisfy the charge balance mechanism with their respective defect sites B 3+ , Li + , O 2- or Cl - , or any combination that satisfies maintaining the charge neutrality of the compound, and wherein, when M includes Al 3+ , M is a binary combination or a ternary combination.
[0017] Another embodiment includes the aforementioned compound, wherein, 0 < x < 2, 0 < y < 6, 0 < z < 1, and 0 < w < 2.
[0018] Another embodiment includes the aforementioned compound, wherein the compound is Li 8 Y 4 B 9 Mo(ClO 12 ) 2 .
[0019] Another embodiment includes the aforementioned compound, wherein the compound is Li 8 Y 4 CrB 9 (ClO 12 ) 2 .
[0020] Another embodiment includes the aforementioned compound, wherein the compound is Li 8 Y 3 B 8 Mo 3 (ClO 12 ) 2 .
[0021] Another embodiment includes the aforementioned compound, wherein M is Fe 3+ , La 3+ , Y 3+ , Mo 3+ , Cr 4+ , As 3+ , Fe 2+ , Mo 4+ , Mo 6 + , As 3- or As 0+One, two or three of the following, or Al 3+ , Fe 3+ ,La 3+ , Y 3+ 、Mo 3+ Cr 4+ 、As 3+ , Fe 2+ 、Mo 4+ 、Mo 6+ 、As 3- or As 0+ Two or three of them.
[0022] Another embodiment includes the aforementioned compound, wherein, M It is a binary combination.
[0023] Another embodiment includes a glass-ceramic composition comprising the foregoing compound.
[0024] Another embodiment includes a lithium ion battery comprising a solid-state ion conductor, wherein the solid-state ion conductor comprises the aforementioned compound. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Example embodiments of the present disclosure will be more clearly understood from the following detailed description taken in conjunction with the accompanying drawings.
[0026] Figure 1A and Figure 1B is a diagram for illustrating an exemplary embodiment of an upper limit of the amount of a dopant.
[0027] Figure 2 It shows that when B 3+ The ideal configuration entropy energy (S ideal ) versus temperature in Kelvin.
[0028] Figure 3 is shown with (A)E hull Graph of an exemplary embodiment of (A) <110 meV / atom and (B) optimized price differential.
[0029] Figure 4 is shown with (A)E hull Graphs of exemplary embodiments of <100 meV / atom and (B) high Li conductivity.
[0030] Figure 5 is shown with (A)E hull Graphs of exemplary embodiments of <100 meV / atom, (B) high Li conductivity, and (C) high moisture stability.
[0031] Figure 6is a diagram illustrating a defect dopant strategy in an exemplary embodiment. DETAILED DESCRIPTION
[0032] The disclosed embodiments described herein are example embodiments, therefore, the disclosure is not limited thereto, and may be implemented in various other forms. Each of the embodiments provided in the following description does not exclude association with one or more features of another example or another embodiment that is also provided herein or is not provided herein but is consistent with the disclosure. For example, even if the matter described in a specific example or embodiment is not described in an example or embodiment different therefrom, unless otherwise mentioned in the description of the matter, the matter may also be understood to be related to or combined with the different examples or embodiments. In addition, it should be understood that all descriptions of the disclosed principles, aspects, examples, and embodiments are intended to cover equivalents of their structure and function. In addition, these equivalents should be understood to include not only currently known equivalents, but also equivalents to be developed in the future.
[0033] As used herein, such as " The expression “at least one of a, b, and c”, when preceding (after) a list of elements, modifies the entire list of elements but does not modify the individual elements in the list. The expression “at least one of a, b, and c” should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.
[0034] The present disclosure provides a parent cubic structure Li 4 B 7 O 12 A non-obvious doping strategy for Cl, in which the parent lithium chloride borax Li 4 B 7 O 12 Tetrahedral BO in Cl 4 The units are partially or completely substituted. These non-obvious substituted compounds are 2 OB 2 O 3 - M x O y -Li-Cl high-dimensional system is formed as a stable main phase in the high-crystallization glass-ceramics. M It can be a trivalent substance, or a mixture of divalent, trivalent, tetravalent or pentavalent substances. Therefore, the compounds of the present disclosure can generally adopt the following chemical forms Li 4-x B 7-y M y O 12-z Cl w , where Li vacancies, O vacancies, and Cl vacancies are allowed, and MIt can be a mono - combination, binary - combination or ternary - combination of the following substances: Al 3+ , Fe 3+ , B 3+ , La 3+ , Y 3+ , Mo 3+ , Be 2+ , Si 4+ , Cr 3+ , As 3+ , Mn 2+ , V 2+ , Co 2+ , Ge 2+ , Fe 2+ , Mo 4+ , Mo 6+ , As 3- , Ti 2+ , P 5+ , As 0+ . Here, 0 < x < 2, 0 < y < 6, 0 < z < 1, 0 < w < 2 can satisfy the charge - balance mechanism with their respective defect sites (B 3+ , Li + , O 2- or Cl - ), or any combination that satisfies maintaining the charge neutrality of the whole composition. The multi - substance doping at the concurrent B 3+ sites and the generation of vacancies of Li, O or Cl increase the configurational entropy (i.e., ~110 meV / atom), which subsequently increases the thermodynamic stability of non - obvious substances at the B 3+ sites.
[0035] The benefits of the concurrent multi - substance doping at the B 3+ sites and the generation of vacancies of Li + , O 2- or Cl - are:
[0036] • Increase the total configurational entropy, reduce the co - existence of BO 4 and MO 4 polyhedral units, and suppress the introduction of large strains in the cation framework, which subsequently increases the stability of non - obvious dopants at the B 3+ sites.
[0037] • Multiple chemical design strategies to minimize the total cost of cubic Li 4-x B 7-y M y O 12-z Cl w while retaining or enhancing the Li - ion conductivity of the parent cubic structure.
[0038] •Maximizing resistance to electrochemical decomposition through the insertion of a diverse collection of species of different oxidation states and sizes, which results in a large increase in configurational entropy.
[0039] •Lower the reduction potential for Li metal, thereby improving Li stability in solid-state batteries.
[0040] • Improve the aqueous stability of the borate structure against water.
[0041] Figure 1A and Figure 1B Reference is made to exemplary embodiments showing an upper limit on the amount of dopant. Figure 1A and Figure 1B The results in the first place show that designing the dopant to be located at B 3+ These results show that in Li 4-x B 7- y M y O 12-z Cl w In the structure, B 3+ The upper limit of the number of dopants that can be accommodated by the site is 3. Therefore, the embodiments of the present disclosure can be 3+ A site has at most 3 substances.
[0042] Therefore, the chemical composition in the present disclosure is to minimize MO by increasing the overall configurational entropy and maintaining the cubic framework of the parent structure. 4 and BO 4 Chemical compositions that minimize polyhedral strain, minimize total material cost, and maintain or increase Li-ion conductivity of the cubic matrix structure:
[0043] Li 4-x B 7-y M y O 12-z Cl w
[0044] Among them, Li vacancies, O vacancies, and Cl vacancies are allowed, and M It can be a one-, two- or three-component combination of the following substances: Al 3+ , Fe 3+ , B 3+ ,La 3+ , Y 3+ 、Mo 3+ 、Be 2+ 、Si 4+ Cr 3+ 、As 3+ , Mn 2+, V 2+ , Co 2+ , Ge 2+ , Fe 2+ , Mo 4+ , Mo 6+ , As 3- , Ti 2+ , P 5+ , As 0+ . Here, 0 < x < 2, 0 < y < 6, 0 < z < 1, 0 < w < 2 can satisfy the charge balance mechanism with their respective defect sites (B 3+ , Li + , O 2- or Cl - ), or any combination that satisfies maintaining the charge neutrality of the entire composition. In another embodiment, 0 ≤ x < 2, 0 < y < 6, 0 ≤ z < 1, and 0 < w < 2.
[0045] The embodiments of the present disclosure can be prepared using standard solid-state methods. In this method, the precursor powders are combined in a certain proportion according to the composition of the target material. As an example, the precursor can be composed of lithium carbonate (Li 2 CO 3 ), boron oxide (B 2 O 3 ), lithium chloride (LiCl), and at least one precursor containing the metal included in M , and as another example, the precursor can be composed of lithium oxide (Li 2 O), boron oxide, lithium chloride, and at least one precursor containing the metal included in M . Examples of metal precursors include metal oxides, metal hydroxides, metal carbonates, and metal nitrates.
[0046] The precursor mixture can be mixed by methods such as ball milling or planetary milling to prepare a homogeneous mixture. The mixing can be carried out in a suitable solvent such as ethanol, isopropyl alcohol, ethylene glycol, or acetone to assist in the uniform dispersion of the precursors.
[0047] Then, the precursor mixture can be heat-treated to an appropriate temperature for an appropriate period of time to prepare a powder with the desired composition and crystal structure. A ceramic composition (such as a glass-ceramic composition) including the powder can be prepared.
[0048] Subsequently, the powder can be compressed using a uniaxial hydraulic press to form a densely extruded pellet. Then, heat treatment can be applied at an appropriate temperature for an appropriate period of time to prepare a dense pellet, which can be used as a solid electrolyte separator in a solid-state lithium battery cell.
[0049] The embodiments of the solid electrolyte membrane mentioned above can be assembled together with the positive electrode active material layer and the negative electrode active material layer for use in an embodiment as a solid-state lithium battery, wherein the solid-state lithium battery includes a positive electrode active material layer, a negative electrode active material layer and a solid electrolyte layer formed between the positive electrode active material layer and the negative electrode active material layer, wherein the solid electrolyte layer includes any of the materials mentioned above.
[0050] Example
[0051] The embodiments will now be described by way of the following examples, which are not intended to limit the embodiments in any way.
[0052] Using high-throughput density functional theory (DFT) calculations, a wide range of non-obvious potential chemical dopants were selected based on their electronegativity, Shannon's crystal radius, and oxidation state. The initial set of potential chemical dopants included 45 species that were selected as follows: 3+ Sc 3+ 、Al 3+ 、Be 2+ , P 5+ Mg 2+ ,La 3+ 、As 3+ , Sr 2+ 、Ti 4+ 、Si 2+ , Fe 3+ 、Mo 3+ , Mn 2+ 、Si 4+ ,Ge 2+ Cr 3+ 、As 0+ 、Mo 6+ 、V 2+ 、As + , P 3+ 、Co 2+ 、Mo 5+ 、As 3- 、Mo 2+ 、As - 、As 2+ 、Ti 2+ 、Mo 4+ , B 2+ , Fe 2+ , B + ,La 2+ , P 4+ 、As 2- , B 3- 、Se 2- Cr 2+ Cr5+ , P + ,Ge 4+ 、V 5 + Cr 4+ 、V 4+ .
[0053] The energy above the linear combination of stable phases (also called the energy above the hull, E hull )) to estimate the phase stability of the predicted material. A phase diagram was constructed using energies calculated using DFT and thermodynamic data from the Materials Project using the Materials Application Programming Interface (API). In order to determine the threshold (Li 4-x B 7-y M y O 12-z Cl w Theoretical compositions in chemical space are considered unstable above this threshold), using the entropy of ideal configuration ( ),in K b is the Boltzmann constant, p i is the probability of each state (occupied or unoccupied), and the sum covers all states of each site. Figure 2 shows a linear dependence of the ideal configuration entropy on a given experimental temperature. It should be noted that previous reports have suggested that the melt-quench-crystallization method can be used to perform the “ 3+ Opposite 4 B 7 Cl 12 O is doped into the cubic matrix structure", where the initial reactant powder is Li 2 CO 3 :Al 2 O 3 :B 2 O 3 :LiCl mixed and at 1150 C. So, assuming 1000 The ideal configuration entropy at C is an effective indicator of the threshold above which the compound being calculated is considered unstable. Specifically, according to Figure 2 (It shows that when B 3+ The ideal configuration entropy energy (S) of the site with three dopants inserted relative to the temperature in Kelvin 理想)), the threshold is set to about 110 meV / atom.
[0054] Figure 3 Shown with (A) E hull <110meV / atom and (B) an exemplary embodiment of optimizing price difference. Specifically, Figure 3 Demonstrating low-cost multicomponent Li 4-x B 7-y M y O 12-z Cl w optimization, where the composition and content are tailored to increase configurational entropy, reduce lattice strain, and introduce cheaper elements (such as Fe). The increase in configurational entropy leads to higher E hull stabilization of the phase.
[0055] Assume the following dummy substances: - A with oxidation state 0+ - D with oxidation state 3+ / - - X with oxidation state 2+ - E with oxidation state 4+ - G with oxidation state 5+ - Z with oxidation state 6+ Public chemical space: -Cl-Li-OD -Cl-Li-OXDE -Cl-Li-OXDG -Cl-Li-OADZ -Cl-Li-ODZ The following stoichiometric ranges are disclosed: - D from 0 to 0.86: ○ Al 3+ →[0,0.5] ○ B 3+ →[0,0.86] ○ Fe 3+ ,La 3+ , Y 3+ →[0,0.43] ○ Mo 3+ →[0,0.36] ○ Cr 3+ →[0,0.21] ○ As 3+ →[0,0.86] ○ As 3- →[0,0.08] - X from 0 to 0.43: ○ Be 2+ →[0,0.43] ○ Mn 2+ →[0,0.22] ○ V 2+ / Co 2+ / Fe 2+ →[0,0.14] ○ Ge 2+ / Ti 2+ →[0,0.07] - E from 0 to 0.43: ○ Si 4+ →[0,0.43] ○ Mo 4+ →[0,0.14] - Z from 0 to 0.14: ○ Mo 6+ →[0, 0.14] - 0 to 0.14 G: ○ P 5+ →[0,0.14] - A from 0 to 0.14: ○ As 0+ →[0,0.14]
[0056] Specifically, Figure 3 Shown when in B 3+ Thermodynamic stability of B when up to 3 species are inserted into the site 3+ The content of Li was gradually screened to optimize 4-x B 7-y M y O 12-z Cl w Overall, a total of 33 unique chemical spaces (i.e., Al-B-Cl-Fe-Li-O, B-Cl-La-Li-OY, Al-B-Cl-Li-Mo-O, B-Cl-Fe-Li-Mo-O, etc.) present E with less than 110 meV / atom hull Table 1 shows the composition of the general formula Li 4-x B 7-y M y O 12-z Cl w A list of representative compositions.
[0057] Table 1. List of representative compositions of the present disclosure
[0058] Figure 4 Shown with (A) E hull <100meV / atom and (B) high Li conductivity exemplary embodiments. Specifically, Figure 4 Shows low E hull Multicomponent Li 4-x B 7-y M y O 12-z Cl w Optimization of the composition, where the content of the composition is tailored to increase the Li-ion conductivity.
[0059] Assume the following fictitious substance: - A with oxidation state 0+ - D with oxidation state 3+ / - - X with oxidation state 2+ - E with oxidation state 4+ - G with oxidation state 5+ - Z with oxidation state 6+ Public chemical space: - Li-Cl-OD|Cl-Li-OXDE|Cl-Li-ODGX|Cl-Li-OADZ The following stoichiometric ranges are disclosed: - D from 0 to 0.86: ○ Al 3+ →[0,0.5] ○ Fe 3+ →[0,0.43] ○ La 3+ →[0,0.29] ○ Y 3+ →[0,0.36] ○ B 3+ →[0,0.86] ○ Mo 3+ →[0,0.36] ○ Cr 3+ →[0,0.21] ○ As 3+ →[0,0.65] - X from 0 to 0.43: ○ Be 2+ →[0,0.43] ○ Mn 2+ →[0,0.22] ○ V 2+ / Co 2+ / Fe 2+ →[0,0.14] ○ Ge 2+ / Ti 2+ →[0,0.07] - E from 0 to 0.43: ○ Si 4+ →[0,0.43] ○ Mo 4+ →[0,0.14] - Z from 0 to 0.14: ○ Mo 6+ →[0,0.14] - 0 to 0.14 G: ○ P 5+ →[0,0.14] - A from 0 to 0.14: ○ As 0+ →[0,0.14]
[0060] Figure 5 Shown with (A) E hull <100meV / atom, (B) high Li conductivity, and (C) high moisture stability. Specifically, Figure 5 Shows low E hull Multicomponent Li 4-x B 7-y M y O 12-z Cl w Optimization of the composition, wherein the content of the composition is tailored to increase the stability of the composition against water.
[0061] Assume the following fictitious substance: - A with oxidation state 0+ - D with oxidation state 3+ / - - X with oxidation state 2+ - E with oxidation state 4+ - G with oxidation state 5+ - Z with oxidation state 6+ Public chemical space: - Cl-Li-OD|Cl-Li-ODEX The following stoichiometric ranges are disclosed: - D from 0 to 0.86: ○ Al 3+ →[0,0.5] ○ Fe 3+ →[0,0.43] ○ B 3+ →[0,0.86] ○ La 3+ →[0,0.28] ○ Y 3+ →[0,0.36] ○ Mo 3+ →[0,0.28] ○ Cr 3+ →[0,0.14] ○ As 3+ →[0,0.57] - X from 0 to 0.43: ○ Mn 2+ →[0,0.15] - E from 0 to 0.43: ○ Si 4+ →[0,0.14]
[0062] Table 2 shows the hull List of example compositions of exemplary embodiments of (A) <100 meV / atom, (B) high Li conductivity, and (C) high moisture stability.
[0063] Table 2, with (A) E hull List of examples of (A) <100 meV / atom, (B) high Li conductivity, and (C) high moisture stability.
[0064] Figure 6 is a diagram illustrating a defect dopant strategy in an exemplary embodiment. Figure 6 The results shown in Figure 2 demonstrate a defect dopant strategy to introduce Cl - Empty space and some small 1 / 2O 2- Li vacancies to balance + Vacant seat.
[0065] The foregoing is an illustration of exemplary embodiments and is not to be construed as limiting the disclosure. Although a few exemplary embodiments have been described, those skilled in the art will readily appreciate that many modifications are possible in the above-described embodiments without materially departing from the disclosure.
Claims
1. A formula is Li 4-x B 7-y M y O 12-z Cl w The compound in, Li vacancies, O vacancies, and Cl vacancies are allowed, and M It is a univalent, binary or ternary combination of the following substances: Al 3+ , Fe 3+ , B 3+ ,La 3+ , Y 3+ 、Mo 3+ 、Be 2+ 、Si 4+ Cr 3+ 、As 3+ , Mn 2+ 、V 2+ 、Co 2+ ,Ge 2+ , Fe 2+ 、Mo 4+ 、Mo 6+ 、As 3- 、Ti 2+ , P 5+ 、As 0+ ,and where 0 ≤ x < 2, 0 < y < 6, 0 ≤ z < 1, and 0 < w < 2 satisfy the charge balance mechanism with their respective defect sites B 3+ , Li + , O 2- or Cl - , or any combination that satisfies maintaining the charge neutrality of the compound, and Among them, when M Including Al 3+ hour, M It is a binary or ternary combination.
2. The compound according to claim 1, wherein 0 < x < 2, 0 < y < 6, 0 < z < 1, and 0 < w < 2.
3. The compound according to claim 1, wherein The compound is Li8Y4B9Mo(ClO 12 )2.
4. The compound according to claim 1, wherein The compound is Li8Y4CrB9(ClO 12 )2.
5. The compound according to claim 1, wherein The compound is Li8Y3B8Mo3(ClO 12 )2.
6. The compound according to claim 1, wherein M It is Fe 3+ ,La 3+ , Y 3+ 、Mo 3+ Cr 3+ 、As 3+ , Fe 2+ 、Mo 4+ 、Mo 6 + 、As 3- and As 0+ One, two or three of the following, or Al 3+ , Fe 3+ ,La 3+ , Y 3+ 、Mo 3+ Cr 3+ 、As 3+ , Fe 2+ 、Mo 4+ 、Mo 6+ 、As 3- and As 0+ Two or three of them.
7. The compound according to claim 6, wherein M It is a binary combination.
8. The compound according to claim 1, wherein M It is a binary combination.
9. A glass-ceramic composition comprising the compound according to claim 1.
10. A glass-ceramic composition comprising the compound according to claim 2.
11. A glass-ceramic composition comprising the compound according to claim 7.
12. A glass-ceramic composition comprising the compound according to claim 8.
13. A lithium ion battery comprising a solid ion conductor, wherein: The solid-state ion conductor comprises the compound according to claim 1.
14. A lithium ion battery comprising a solid ion conductor, wherein: The solid-state ion conductor comprises the compound according to claim 2.
15. A lithium ion battery comprising a solid ion conductor, wherein: The solid-state ion conductor comprises the compound according to claim 3.
16. A lithium ion battery comprising a solid ion conductor, wherein: The solid-state ion conductor comprises the compound according to claim 4.
17. A lithium ion battery comprising a solid ion conductor, wherein: The solid-state ion conductor comprises the compound according to claim 5.
18. A lithium ion battery comprising a solid ion conductor, wherein: The solid-state ion conductor comprises the compound according to claim 6.
19. A lithium ion battery comprising a solid ion conductor, wherein: The solid-state ion conductor comprises the compound according to claim 7.
20. A lithium ion battery comprising a solid ion conductor, wherein: The solid-state ion conductor comprises the compound according to claim 8.